Administration of Traditional Chinese Blood Circulation Activating Drugs for Microvascular Complications in Patients with Type 2 Diabetes Mellitus - Lisha He; Han Wang; Chengjuan Gu; Xinhui He; Linhua Zhao; Xiaolin Tong (Journal of Diabetes Research)
Traditional Chinese medicine (TCM) is an important complementary strategy for treating diabetes mellitus (DM) in China. Traditional Chinese blood circulation activating drugs are intended to guide an overall approach to the prevention and treatment of microvascular complications of DM. The core mechanism is related to the protection of the vascular endothelium and the basement membrane. Here, we reviewed the scientific evidence underpinning the use of blood circulation activating drugs to prevent and treat DM-induced microvascular complications, including diabetic nephropathy (DN), diabetic peripheral neuropathy (DPN), and diabetic retinopathy (DR). Furthermore, we summarized the effects and mechanism of TCM on improving blood rheology, inhibiting aggregation of platelet, forming advanced glycation end products (AGEs), regulating oxidative stress, reducing blood fat, and improving lipid metabolism. The paper provides a new theoretical basis for the clinical practice of TCM in the prevention and treatment of DM and its microvascular complications.